Custeio baseado em atividades na gestão de uma instituição prestadora de serviços educacionais - Ribeiro, Rogeane Morais (2011)
With the constant transformations in the scene of the institutions of higher education the present work has as general objective to consider a model of verification and management of costs for institutions of higher education (IHE), managed for a focus control in the strategy itself , that makes possible the visualization of future scenes, contributing for the improvement of its performance front to the challenges that appear with the expansion of the education. In addition to identify, by means of bibliographical survey, the main used methods of costings; to present a model of identification and control of costs that are simultaneous with the activities of this institution; to inquire the possibility of execution of the model, through the application in the Institute of Studies and Pesquisas Sobralense (IEPS) and to scenes for the next the five years to the institutions. To reach the considered objectives, they are overcome for reference given by the data from MEC/INEP (2008), that show the acceleration of the growth in the period of 1997 the 2006, from the promulgation of the LDB, and the relation between the universities and the support institutes, the so called third sector, being the model of Expenditure Based on Activity (ABC) considered by Peter (2001), adapted for implantation in the IEPS. In complement it was based in the theory of prospection of scenes argued by Sheep (2010) and Fort (2001). The methodology of the research is of descriptive, classified boarding as bibliographical, documentary and of field, with qualitative and quantitative nature. The selected universe as respondent had been the managers who exert management functions, administrative, pedagogical and of assessorship. The tools for the data collection were given by means of questionnaires half-structuralized with specific boarding for each respondent. The interpretation and treatment of the data were carried through by means of analysis of content and statistical treatment. The results had indicated the necessity of reorganization in the managemental processes of the IEPS, through a strategical planning and consequently the implantation of an costing system, which will assist the general direction and the coordenadorias of the institute in the accompaniment of the activities of the headquarters and the units of extension, that meets in little representative positioning in the educational market, leaving to desire in the direction of one real coherent presentation between the mission and the offered services the society. Ahead of the analysis of the scenes of 2006-2010 and 2011-2015, it was visualized that the institution although a 10% evasion a year, kept a considerable prescription, but they see using itself of strategies little, that is, that they do not provide to competitive and sustainable differential in search of growth and superior position. It is surveyed that this work answers partially to the formulated question, in view of the limitations identified in the passage of the metodologic elaboration.